Serum Activity of Liver Enzymes Is Associated With Higher Mortality in COVID-19: A Systematic Review and Meta-Analysis - Boregowda, Umesha; Aloysius, Mark M.; Perisetti, Abhilash; Gajendran, Mahesh; Bansal, Pardeep; Goyal, Hemant (Frontiers in Medicine, 2020)
Background: Abnormal liver chemistries are common findings in patients with COVID-19. It is unclear whether abnormal liver chemistries can predict severity of COVID-19. Therefore, we compared the abnormalities of the component of liver chemistries such as hepatic transaminases, total bilirubin, albumin, and prothrombin time in COVID-19 to evaluate if these are associated with severity and mortality. Methods: An electronic search was performed on PubMed/Medline, EMBASE, and Google Scholar for studies comparing liver chemistries in severe and mild COVID-19. The literature search was performed using keywords ‘COVID-19,’ ‘Liver,’ Aspartate Aminotransferase (AST),’ and ‘Alanine Aminotransferase (ALT),’ ‘AST,’ and ‘ALT,’ in various combinations of ‘AND/OR’ from December 1, 2019, till May 8, 2020. The pooled weighted mean difference (WMD) and 95% confidence interval (CI) were calculated for each component of liver chemistries. Results: Twenty-two studies were eligible, with 3256 patients (54.57% males). Seventeen studies compared liver chemistries for severe vs. mild COVID-19, whereas five studies compared liver chemistries in survival vs. non-survival groups. The pooled WMD of AST and ALT in severe vs. mild COVID-19 was 12.23 (95% CI; 8.07, 16.39; p<0.01) and 8.07 (95% CI 2.55, 11.91; p<0.01), respectively. The pooled WMD for AST in survivors vs. non-survivors analysis was 8.82 (n=789; 95% CI; 2.27, 15.37; p<0.01) and that of ALT was 4.70 (n=340; 95% CI 0.04,9.35; p=0.05). Conclusion: Our meta-analysis shows that deranged liver chemistries may indicate severe COVID-19 and could also predict mortality. Larger studies are needed to evaluate the relationship between derangement in liver chemistries and mortality in COVID-19.